Production and Utilization of Vermicompost in Agro Industry - M. Lekeshmanaswamy, G. Nithya* and (Journal of Phytology, 2010)
SUMMARY Vermicompost was prepared by using the earthworms, Eudrilus eugeniae collected from the Sathyamangalam, Erode district and it is maintained under normal laboratory conditions. The compost was prepared in large amount and the rate of compost was noted for eight months from the months of October 2005 to May 2006. After production of the compost, required amount of compost was taken for the growth of vegetables like Solanum melongena (Brinjal), Capsicum minimum (Chilli), Alysicarpus spinosus (Mullakeerai) and Amaranthus viridis (Pachathandukeerai) were observed using 2kgs of garden soil along with 1kgs of vermicompost (in the ratio 2:1). The results showed higher percentage of biomass production in the vermicompost medium (Experiment) when compared to the garden soil (Control). Due to their short life span some plants in the experimental medium showed high growth rate in short period. Key words: Eudrilus eugeniae, Vermicompost, Solanum melongena, Capsicum minimum, Alysicarpus spinosus, Amaranthus viridis <span style="font-weight: normal; font-size: 7pt; line-height: 110%; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-variant: normal! important; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">G. Nithya and M. Lekeshmanaswamy. Production and Utilization of Vermicompost in Agro Industry. Â J Phytol 2/2 (2010) 68-72.